1989
DOI: 10.1111/j.1744-313x.1989.tb00485.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL SIGNIFICANCE OF BETA hCG, HLA AND OTHER MEMBRANE ANTIGEN EXPRESSION ON BLADDER TUMOURS AND THEIR RELATIONSHIP TO TUMOUR INFILTRATING LYMPHOCYTES (TIL)

Abstract: SUMMARY Expression of beta human chorionic gonadotropin (βhCG) by bladder tumours has been shown to be associated with increased metastases and resistance to treatment with radiotherapy and chemotherapy. Preliminary results from typing frozen tumours using monoclonal antibodies against HLA determinants show reduced or lost expression of one or more antigens in two thirds of patients studied with a trend for more malignant behaviour and inability to generate tumour infiltrating lymphocyte expression using Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…42-46 The efficacy of vaccination may be further improved by engineering the tumor cells to engage immunostimulatory molecules such as GM-CSF, CD40, CD80, CD83, CD137 etc. 4-6, 47-49 However, to achieve therapeutic efficacy against tumors which are larger than a few mm in diameter, the powerful immunosuppressive mechanisms at tumor sites need to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…42-46 The efficacy of vaccination may be further improved by engineering the tumor cells to engage immunostimulatory molecules such as GM-CSF, CD40, CD80, CD83, CD137 etc. 4-6, 47-49 However, to achieve therapeutic efficacy against tumors which are larger than a few mm in diameter, the powerful immunosuppressive mechanisms at tumor sites need to be overcome.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to find out whether the same is true when using dendritic cells that have been pulsed 11 or transfected 9 with tumor material. We hypothesize that the situation may be similar for other members of the TGFb family and other tumor-produced immunosuppressive molecules including hCG 40 and B7-H-1. 41 We further hypothesize that the efficacy of vaccination can be improved by transfecting tumor cells whose production of immunosuppressive factors has been inhibited to also engage immunostimulatory signals, for example, via CD80, 14 anti-CD137scFv, 16 CD83, 17 or granulocyte-macrophage colony-stimulating factor.…”
Section: Discussionmentioning
confidence: 95%
“…Preliminary information from our own work has demonstrated more frequent reactivity of anti-HPV16 E7 antibody with superficial than invasive tumour (Oliver, 1989). As loss of HLA class I is also more frequent in invasive tumours (Nouri et al, 1990), it is possible that HPV antigen in association with appropriate HLA could be explored as possible vaccine for cancer patients (Anon, 1989).…”
mentioning
confidence: 99%
“…One possible factor explaining this has come from the recent studies in bladder cancer. These have demonstrated that more than 50% of bladder tumours have variable degrees of polymorphic or monomorphic HLA class I antigen loss (Nouri et al, 1990) as an immune escape mechanism in association with P h C G expression (Oliver et al, 1989). This paper set out to study generation of TILs from bladder cancer biopsies and investigated the influence of HLA class I expression on the ability to generate TILs.…”
mentioning
confidence: 99%